ANALYSIS OF MOTOR-GRADER LOADING ON THE BASIS OF FRACTAL DIMENSION - Polyarus, A.; Paschenko, R.; Poliakov, Е.; Lebedinskyi, A.; Полярус, О. В.; Пащенко, Р. Е.; Поляков, Є. О.; Лебединський, А. В.; Полярус, А. В.; Пащенко, Р. Э.; Поляков, Е. А.; Лебединский, А. В. (Харьковский национальный автомобильно-дорожный университет, 2016)
The possibility of fractal dimension application for analysis of grader loading modes is con-sidered in the article. The fractal dimensions of experimental dependences of load on the coupling pin of the grader at its different working conditions are calculated. It is determined that the magnitude of the fractal dimension allows to estimate the highest and lowest load of the grader.
АНАЛІЗ НАВАНТАЖЕННЯ АВТОГРЕЙДЕРА НА ОСНОВІ ФРАКТАЛЬНОЇ РОЗМІРНОСТІ
АНАЛИЗ НАГРУЗКИ АВТОГРЕЙДЕРА НА ОСНОВЕ ФРАКТАЛЬНОЙ РАЗМЕРНОСТИ
Keywords: fractal dimension; grader blade; load mode; фрактальна розмірність; відвал автогрейдера; режим навантаження; 625.76.08 : 517.938